2006
DOI: 10.1111/j.1420-9101.2006.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of theChorthippus parallelushybrid zone: chromosomal evidence of multiple refugia for Iberian populations

Abstract: A study of the variation in pattern and frequency of constitutive heterochromatin and nucleolar organizing regions of the X chromosomes of male Chorthippus parallelus grasshoppers in 25 populations within the Iberian peninsula requires us to revise our interpretation of the biogeography and evolutionary history of this species. Hybridization between the subspecies Cp erythropus and Cp parallelus, previously only known from populations in the Pyrenean cols, is shown to extend at least 400 km further into north‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…An exhaustive list can be found in Gómez and Lunt (2007, and references therein). Recently, further evidence supporting this theory included the rotifer Brachionus plicatilis (Campillo et al 2011), the grasshopper Chorthippus parallelus (Bella et al 2007), the Mediterranean toad (Alytes cisternasii) (Gonçalves et al 2009), the red-legged partridge (Alectoris rufa) (Ferrero et al 2011), the field vole, Microtus agrestis (Jaarola and Searle 2003), and the southern water vole (Arvicola sapidus) (Centeno-Cuadros et al 2009). …”
Section: Trends In Western Iberian Phylogeographymentioning
confidence: 94%
“…An exhaustive list can be found in Gómez and Lunt (2007, and references therein). Recently, further evidence supporting this theory included the rotifer Brachionus plicatilis (Campillo et al 2011), the grasshopper Chorthippus parallelus (Bella et al 2007), the Mediterranean toad (Alytes cisternasii) (Gonçalves et al 2009), the red-legged partridge (Alectoris rufa) (Ferrero et al 2011), the field vole, Microtus agrestis (Jaarola and Searle 2003), and the southern water vole (Arvicola sapidus) (Centeno-Cuadros et al 2009). …”
Section: Trends In Western Iberian Phylogeographymentioning
confidence: 94%
“…Many studies have showed clines in this hybrid zone of morphological, ethological, chromosomal and molecular markers that differentiate the subspecies (Butlin and Hewitt, 1985a, b;Gosálvez et al, 1988;Ritchie, 1990;Cooper et al, 1995;Lunt et al, 1998;Ibrahim et al, 2002;Bella et al, 2007). Furthermore, laboratory crosses between these subspecies produce male F1 hybrids that are sterile, exhibiting testicular dysfunction and meiotic anomalies (Hewitt et al, 1987;Bella et al, 1990;Virdee and Hewitt, 1994;Shuker et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…While F1 hybrid males produced in the laboratory are sterile in accordance with Haldane’s rule (Hewitt et al 1987; Bella et al 1990), hybrids inhabiting the contact zones are generally fit, viable and fertile after generations of coadaptation of genes from both pure species within a hybrid genome. Several studies have defined morphological, ethological, chromosomal, and molecular differences between the two subspecies that are used as markers of each Cp subspecies and their hybrids (Butlin and Hewitt 1985a, b; Gosálvez et al 1988; Ritchie 1990; Cooper et al 1995; Lunt et al 1998; Ibrahim et al 2002; Bella et al 2007; see Shuker et al 2005 for a review). Of all the reported markers, the cytogenetic X-linked ones are those that show the most striking differences between Cpp and Cpe subspecies: the distribution and/or composition of the heterochromatic regions differ between the Cpp and Cpe X chromosomes, including an extra Nucleolar Organizing Region (NOR) present only in Cpp (Gosálvez et al 1988; Serrano et al 1996; Bella et al 1993, 2007).…”
Section: Introductionmentioning
confidence: 99%